RETRACTED ARTICLE: Novel drug delivery system based on doxorubicin-encapsulated magnetic nanoparticles modified with PLGA-PEG1000 copolymer. (2nd January 2016) - Ebrahimi, Eommolbanin; Akbarzadeh, Abolfazl; Abbasi, Elham; Khandaghi, Amir Ahmad; Abasalizadeh, Farhad; Davaran, Soodabeh
Abstract : We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Eommolbanin Ebrahimi, Abolfazl Akbarzadeh, Elham Abbasi, Amir Ahmad Khandaghi, Farhad Abasalizadeh & Soodabeh Davaran (2016) Novel drug delivery system based on doxorubicin-encapsulated magnetic nanoparticles modified with PLGA-PEG1000 copolymer. Artificial Cells, Nanomedicine, and Biotechnology, 44(1), 290–297, DOI: 10.3109/21691401.2014.944646 Since publication, a reader alerted the Publisher that Figures 5, 6 and 7 appear to have been previously published in Artificial Cells, Nanomedicine, and Biotechnology and other journals, specifically: Figure 5 appears to have been duplicated with Figure 6 from Ebrahimi et al., 2014 (https://doi.org/10.3109/21691401.2014.968822 ). Figure 6 appears to have been duplicated with Figure 7 from Ebrahimi et al., 2014 (https://doi.org/10.3109/21691401.2014.968822 ) Figure 6 appears to have been duplicated with Figure 11 from Akbarzadeh et al., 2012 (https://doi.org/10.2147/IJN.S24326 ) Figure 7 appears to have been duplicated with Figure 8 from Ebrahimi et al., 2014 (https://doi.org/10.3109/21691401.2014.968822 ). The reused images have been described as originating from a new study with no reference to the previous studies. We contacted the corresponding author and second author, and they acknowledged the similarities in the data published. As this error directly impacts the reported results and conclusions, the Editor and Publisher have agreed to retract the article to ensure correction of the scholarly record. The corresponding author has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.